2017
DOI: 10.4028/www.scientific.net/ddf.375.84
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Chemical Diffusion Coefficients of (U, Pu)O<sub>2-x</sub>

Abstract: The oxygen chemical diffusion coefficient in (U, Pu)O2-x was determined by thermo-gravimetry as functions of the Pu content, oxygen-to-metal ratio and temperature. The surface reaction was considered in the diffusion coefficient determination. The activation energy for the chemical diffusion coefficient was 60 kJ/mol and 65 kJ/mol, respectively, in (U0.8Pu0.2)O2-x and (U0.7Pu0.3)O2-x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Indeed, oxygen chemical diffusion in AnO 2±x was shown to be enhanced at compositions close to O/M = 2.00 (Chereau and Wadier, 1973;Sari, 1978;Bayoǧlu and Lorenzelli, 1979;Bayoǧlu and Lorenzelli, 1984;Stan and Cristea, 2005) as a result of preponderant clustering when the deviation from stoichiometry is increased. This observation remains under discussion among the community as some other studies suggest either an increase or a stagnation in the oxygen chemical diffusion coefficient when the deviation from stoichiometry is increased (Woodley and Gibby, 1973;Kim and Olander, 1981;Kato et al, 2013;Vauchy et al, 2015b;Watanabe et al, 2015;Watanabe et al, 2017).…”
Section: Oxygen/metal Ratio Oxygen Potential Points Defects Clusters ...mentioning
confidence: 94%
“…Indeed, oxygen chemical diffusion in AnO 2±x was shown to be enhanced at compositions close to O/M = 2.00 (Chereau and Wadier, 1973;Sari, 1978;Bayoǧlu and Lorenzelli, 1979;Bayoǧlu and Lorenzelli, 1984;Stan and Cristea, 2005) as a result of preponderant clustering when the deviation from stoichiometry is increased. This observation remains under discussion among the community as some other studies suggest either an increase or a stagnation in the oxygen chemical diffusion coefficient when the deviation from stoichiometry is increased (Woodley and Gibby, 1973;Kim and Olander, 1981;Kato et al, 2013;Vauchy et al, 2015b;Watanabe et al, 2015;Watanabe et al, 2017).…”
Section: Oxygen/metal Ratio Oxygen Potential Points Defects Clusters ...mentioning
confidence: 94%
“…Previous studies have measured oxygen self-diffusion and chemical diffusion coefficients (Watanabe et al, 2017;Vauchy et al, 2015;Sari, 1978;Murch and Catlow, 1987;Lorenzelli and El Sayed Ali, 1977;Kato et al, 2013;Kato et al, 2009;Garcia et al, 2010;Deaton and Wiedenheft, 1973;D'Annucci and Sari, 1977;Contamin et al, 1972;Breitung, 1978;Belle, 1969;Bayoglu and Lorenzelli, 1984;Bayoglu and Lorenzelli, 1979;Auskern and Belle, 1961;Ando et al, 1976;Watanabe and Kato, 2012;Kim and Olander, 1981;Floyd, 1973;Kamiya et al, 2000;Millot and Mierry, 1985;Gotte et al, 2007). The oxygen diffusion coefficients data set used in this review is shown in Table A1.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…The data were measured using various methods, such as the isotope method, thermogravimetry, electrical conductivity measurement, and thermal dilatometry. It was difficult to assess changes dependent on temperature and O/M ratio because the data were scattered (Floyd, 1973;Gotte et al, 2007;Kamiya et al, 2000;Millot and Mierry, 1985;Ando et al, 1976;Dornelas and Lacombe, 1967;Matzke, 1987;Ligeon et al, 1970;Dorado et al, 2011;Lay, 1970;Bittel et al, 1969;Ruello et al, 2004;Kato et al, 2013;Mullins, 1972;Deaton and Wiedenheft, 1973;Bayoglu et al, 1983;Bayoglu and Lorenzelli, 1979;Chereau and Wadier, 1973;Bayoglu and Lorenzelli, 1980;Bayoglu and Lorenzelli, 1984;D'Annucci and Sari, 1977;Kato et al, 2009;Watanabe et al, 2017;Watanabe et al, 2020;Vauchy et al, 2015).…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation